2013
DOI: 10.1073/pnas.1313433110
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Slo1 K + channels with and without the gating ring

Abstract: High-conductance Ca 2+-and voltage-activated K + (Slo1 or BK) channels (KCNMA1) play key roles in many physiological processes. The structure of the Slo1 channel has two functional domains, a core consisting of four voltage sensors controlling an ion-conducting pore, and a larger tail that forms an intracellular gating ring thought to confer Ca 2+ and Mg 2+ sensitivity as well as sensitivity to a host of other intracellular factors. Although the modular structure of the Slo1 channel is known, the functional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 47 publications
2
65
0
Order By: Relevance
“…This description is meant to capture an important property of the structures; that the voltage sensor communicates with the Ca 2+ sensor. However, experiments under extreme conditions of voltage and Ca 2+ have shown that each sensor to some degree can work independently to regulate the pore 4,23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This description is meant to capture an important property of the structures; that the voltage sensor communicates with the Ca 2+ sensor. However, experiments under extreme conditions of voltage and Ca 2+ have shown that each sensor to some degree can work independently to regulate the pore 4,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The S4–S5 linker is one of the key structural elements on the TMD side of the interface and therefore movements of S4 helices should directly impinge on movements of the RCK1 N-lobes on the gating ring. The interface also contains a Mg 2+ ion, whose binding site was predicted by mutagenesis studies 10,15,18,19,20,21,22,23 . In the Ca 2+ structure the Mg 2+ ion mediates multiple interactions that bridge the RCK1 N-lobe to the TMD via helix S0’ and the S2–S3 linker (Fig.…”
Section: Regulation By Voltagementioning
confidence: 99%
“…Ca 2+ binding through these domains is transduced to the transmembrane domain via the S6/RCK1 linker (12,17). Recent evidence (18) supports the idea that the cytosolic domain of this channel is responsible for sensing Ca 2+ , because truncated BK channels lacking the C terminus are insensitive to Ca…”
Section: +mentioning
confidence: 93%
“…Left shift of G-V (V0.5 Table 1: C-linker scrambling mutations and measured V0.5 in the full-length and Core-MT BK channels at [Ca 2+ ] = 0 and [Mg 2+ ] = 0. The Core-MT constructs are based on the TMD, C-linker of mSlo1, and an 11-residue tail from KV 1.4 of the mouse Shaker family (19,20). The location of the nearest Tyr to the S6 C-terminal is highlighted in green.…”
Section: Sequence Scrambling Of the C-linker Dramatically Modulates Bmentioning
confidence: 99%